1997
DOI: 10.1007/s004660050241
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of conforming BEM algorithms for hypersingular boundary integral equations

Abstract: The widely held notion that the use of standard conforming isoparametric boundary elements may not be used in the solution of hypersingular integral equations is investigated. It is demonstrated that for points on the boundary where the underlying ®eld is C 1Ya continuous, a class of rigorous nonsingular conforming BEM algorithms may be applied. The justi®cation for this class of algorithms is interpreted in terms of some recent criticism. It is shown that the numerical integration in these conforming BEM algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…In spite of the very successful numerical results reported by Richardson et al (1997), Richardson and Cruse (1999), Chien et al (1991), Huang and Cruse (1994) using various forms of these relaxed algorithms combined with piece-wise C 1,α interpolations, Martin and Rizzo (1996), Krishnasamy et al (1992) have concluded that these algorithms could not be theoretically justified. This means that, from a strictly mathematical point of view, only boundary element implementations that ensure C 0,α or C 1,α continuity at each collocation point can be applied in the discretizations of the standard, or the hypersingular boundary integral equations, respectively.…”
Section: Paper Accepted April 2009 Technical Editor: Nestor a Zouamentioning
confidence: 97%
See 3 more Smart Citations
“…In spite of the very successful numerical results reported by Richardson et al (1997), Richardson and Cruse (1999), Chien et al (1991), Huang and Cruse (1994) using various forms of these relaxed algorithms combined with piece-wise C 1,α interpolations, Martin and Rizzo (1996), Krishnasamy et al (1992) have concluded that these algorithms could not be theoretically justified. This means that, from a strictly mathematical point of view, only boundary element implementations that ensure C 0,α or C 1,α continuity at each collocation point can be applied in the discretizations of the standard, or the hypersingular boundary integral equations, respectively.…”
Section: Paper Accepted April 2009 Technical Editor: Nestor a Zouamentioning
confidence: 97%
“…The next section discusses the discretization of these integral equations, where the boundary is discretized into standard isoparametric elements, which satisfy all the continuity requirements for the potential-BIE, but do not satisfy the continuity requirements for the flux-BIE at a finite number of inter-element nodes in case standard continuous isoparametric boundary elements are used. Since these continuity requirements refer only to collocation points, a 'relaxed continuity' approach is introduced for the case of collocation at an inter-element node according to Huang and Cruse (1994), Cruse and Richardson (1996), Richardson et al (1997), Richardson and Cruse (1999), and different alternatives are discussed, which either allow or avoid the collocation at such nodes. Numerical results obtained from these alternatives, as well as from the self-regular potential BIE are presented.…”
Section: Self-regular Bie For 2-d Potential Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the third author has written several papers with Huang and Richardson [2][3][4] in which they do so collocate. In fact, they report good numerical computations (see also References 5 and 6), using regularized integral equations.…”
Section: Introductionmentioning
confidence: 93%